A detailed protocol for a rapid analysis of testicular cell populations using flow cytometry. (7th August 2015) - Rotgers, E.; Cisneros‐Montalvo, S.; Jahnukainen, K.; Sandholm, J.; Toppari, J.; Nurmio, M.
Summary Accurate analysis and quantification of different testicular cell populations are of central importance in studies of male reproductive biology. The traditional histomorphometric and immunohistochemical methods remain the gold standard in studying the complex dynamics of the testicular tissue. Through past years advances have been made in the application of flow cytometry for the rapid analysis of testicular cell populations. Detection of DNA content and of surface antigens and fluorescent reporters have been widely used to analyze and sort cells. Detection of intracellular antigens can broaden the possibilities of applying flow cytometry in studies of male reproduction. Here, we report a detailed protocol for the preparation of rat testicular tissue for detection of intracellular antigens by flow cytometry, and a pipeline for subsequent data analysis and troubleshooting. Rat testicular ontogenesis was chosen as the experimental model to validate the performance of the assay using vimentin and γH2AX as intracellular markers for the somatic and spermatogenic cells, respectively. The results show that the assay is reproducible and recapitulates the rat testis ontogenesis.